Urine protein:creatinine ratio in growing kittens: new insight - Pereira, Marcy Lancia; Paixão, Crysttian Arantes; Carvalho, Marileda Bonafim [UNESP] (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2024)
This study aimed to evaluate the urinary excretion of protein employing the urine protein:creatinine ratio in growing health kittens and included twelve clinically healthy multi-mixed-breed kittens, seven males and five females from three different litters. Urine collections started when the kittens completed the fourth week of life. The study followed a controlled longitudinal experimental model, with 14 repeated measures, one per week. A total of 168 urine samples from 12 healthy growing kittens were analyzed. UPC ratio median value was 0.56 (confidence interval 0.51 - 0.62), revealing urinary protein excretion more remarkable than is expected for healthy adult cats. Two-way repeated-measures ANOVA results indicated no statistically significant differences in urine protein:creatinine ratio values concerning the kittens' ages and genders. Additionally, there was a striking fluctuation of urine protein: creatinine ratio values for all kittens over the 14 weeks (coefficient of variation 53.3%). Urine protein:creatinine ratio of healthy growing kittens changes unexpectedly, and most values reach magnitudes considered pathological for adult cats, suggesting a clinically irrelevant condition. Since the fluctuation of the UPC is not related to age (from the fourth to the seventeenth week of age), to interpret of UPC of growing kittens, in practice or research, it is mandatory to repeat the measures, at least three times, at one week apart, to discharge pathologic event.
Keywords: cat; physiological proteinuria; UPC; urine